Reflection of the Ultra-Wideband Signals from Plasma Layers - Chernogor, L.F.; Lazorenko, O.V. (Радиофизика и радиоастрономия, 2002)
This paper is concerned with the temporal distortion caused by the dispersion of ultra-wideband signals reflecting from linear and parabolic plasma layers. The magnitudes of the expected effects have been estimated for the various parameters of the plasma layers and sounding ultra-wideband signals. The ultra-wideband signal distortions are calculated for reflection from the ionospheric plasma layers and their features are described. Рассмотрены дисперсионные искажения, которые возникают при отражении сверхширокополосных сигналов от линейного и параболического плазменных слоев. Оценены величины наблюдаемых эффектов при различных соотношениях параметров плазменного слоя и зондирующего сверхширокополосного сигнала. Рассчитаны величины и описан характер дисперсионных отражений сверхширокополосных сигналов при отражении от ионосферных плазменных слоев. Розглянуто дисперсійні спотворення, що виникають при відбитті надширокосмугових сигналів від лінійного та параболічного плазмових шарів. Оцінено величини ефектів, що спостерігаються, при різних співвідношеннях параметрів плазмового шару та зондуючого надширокосмугового сигналу. Розраховано величини та описано характер дисперсійних спотворень надширокосмугових сигналів при відбитті від іоносферних плазмових шарів.